Social problems and social change - Suniti Kapadiya (Jaipur Mark Publishers, 2022)
Indian marriage problems and prospects; population problems and beggary; urban sociology; urban ecology and modern society; Indian society and women development; women literacy and social change; lifestyle and social change; social psychology and social problems; research in social psychology.
Keywords: Social problems and services